Evaluation of Revenue Channels and Challenges in Sustainable Management of Oyo State Forest Reserves, Nigeria - R.I. Kolade; A.A. Adejumo; O.O. Olugbire; O.F. Akanni; O.A. Fatoki (Journal of Applied Sciences and Environmental Management, 2020)
Forest revenue system is an instrument used by government to achieve various goals and objectives in forest management. This paper evaluates the various challenges of revenue collection and remittance in Oyo forestry service in Nigeria. A total of 94 forest officials were identified and reached (100%) in all the forestry administrative zones in Oyo State, including the headquarters through a set of structured questionnaire and data obtained were analyzed using descriptive statistics and logit regression at α0.05. Theaverage age of the respondents was 39.7±6.5 years, mostly male (71%), married (75.6%) and had secondary education (63%). Challenges confronting adequate revenue collection included lack of proper law enforcement, payment of cash by revenue collectors and inability of field officers to withstand armed illegal fellers with odds-ratio of 55694.85,  668.78 and 20.79 respectively. Problems facing adequate revenue remittance were remittance by field staff, inaccessibility of bank on time, lack of provision of incentives for running cost by the government and possibilities of field officers indulging in printing of fake receipts with odds-ratio of 140.18, 116.80, 3.65 and 3.44 respectively. The study exposed the various challenges facing adequate revenue collection and remittance in Oyo State forestry service, it is therefore necessary for the forest managers in the State to utilize this information wisely for the betterment of revenue generation.